Leader–Follower Congruence in Work Engagement and Leader–Member Exchange: The Moderating Role of Conscientiousness of Followers - Ye, Yanhua; Wang, Ziwen; Lu, Xiaowei (Frontiers in Psychology, 2021)
Extant research has investigated the relationship between work engagement and various outcomes such as job performance and organizational commitment, neglecting the effect of work engagement on social relationships at work. Drawing upon person-environment fit theory and LMX theory, the present study aims to examine the effect of (in)congruence between leader and follower work engagement on leader-member exchange (LMX) and the moderating effect of conscientiousness. 273 employees and 72 leaders participated in this study and completed the measurements of work engagement, LMX, and conscientiousness at two time points. Using cross-level polynomial regressions, we found that compared with incongruent work engagement, employees perceived high levels of LMX quality when their work engagement was aligned with their leaders’. Regarding the congruence, employees reported higher levels of LMX when congruence in work engagement was at higher rather than lower levels. Regarding the incongruence, when employees engaged less in their work tasks than their leaders, they were more likely to experience lower LMX. Moreover, the negative relationship between incongruence in leader and follower work engagement and LMX was mitigated when followers were more conscientious. All our hypotheses were supported. Both theoretical and practical implications for work engagement as well as future directions are discussed.